2024
DOI: 10.1371/journal.pone.0298584
|View full text |Cite
|
Sign up to set email alerts
|

Double-duty caregivers enduring COVID-19 pandemic to endemic: “It’s just wearing me down”

Jasneet Parmar,
Tanya L’Heureux,
Michelle Lobchuk
et al.

Abstract: The COVID-19 pandemic has considerably strained health care providers and family caregivers. Double-duty caregivers give unpaid care at home and are employed as care providers. This sequential mixed-method study, a survey followed by qualitative interviews, aimed to comprehensively understand the experiences of these Canadian double-duty caregivers amidst the pandemic and the transition to the endemic phase. The multi-section survey included standardized assessments such as the Double-duty Caregiver Scale and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 89 publications
0
1
0
Order By: Relevance
“…We acknowledge that the timeframe (i.e., 2 years from the start to the end of the COVID pandemic) examined in the present study may be too short for a significant increase to be observed in the number of research articles published that examined mental health in women and men. Given that the time for scientific research to go through the peer-review process and ultimately be published has been estimated at 9 months (for STEM fields) to 18 months (for social sciences, arts/humanities, and business/economics; [ 34 ]) future work should re-examine the difference in the number of published research articles that examine mental health in women and men to determine if that disparity changes when viewed at a larger time frame (e.g., 5 or 10 years from the start of the COVID pandemic), and as the pandemic shifts to an endemic [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…We acknowledge that the timeframe (i.e., 2 years from the start to the end of the COVID pandemic) examined in the present study may be too short for a significant increase to be observed in the number of research articles published that examined mental health in women and men. Given that the time for scientific research to go through the peer-review process and ultimately be published has been estimated at 9 months (for STEM fields) to 18 months (for social sciences, arts/humanities, and business/economics; [ 34 ]) future work should re-examine the difference in the number of published research articles that examine mental health in women and men to determine if that disparity changes when viewed at a larger time frame (e.g., 5 or 10 years from the start of the COVID pandemic), and as the pandemic shifts to an endemic [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…The COVID-19 pandemic complicated DDCs’ health and wellbeing [ 10 ]. Research illustrates that, during the pandemic, 63% of carers reported an increase in unpaid caregiving duties due to a myriad factors, including an increase in the needs of dependents and difficulty accessing health services [ 11 ].…”
Section: Introductionmentioning
confidence: 99%